Analisis Perubahan Tap Trafo Unit 2 PLTG Payo Selincah untuk Memenuhi Kelayakan Sinkronisasi saat Tegangan Sistem Melebihi 153 kV - Denny Boy Panggabean; Haris Gunawan; Dino Erivianto (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Synchronization between power plants and interconnected systems requires matching voltage, frequency, and phase angle parameters. At the Payo Selincah Unit 2 Gas Turbine Power Plant (PLTG), synchronization often encounters issues due to transmission system voltage frequently exceeding 153 kV. This study aims to analyze the need for adjusting the tap position of the 11.5 kV/150 kV step-up transformer to ensure synchronization is still possible even under overvoltage conditions. The methodology includes a literature review, field testing, and TTR (Tap Transformer Ratio) analysis based on voltage readings from the HV (High Voltage) and LV (Low Voltage) sides. The results show that changing from Tap 3 to Tap 2 reduces the LV side voltage from 19.89 kV to 19.42 kV, while the HV side voltage drops from 11.93 kV to 11.65 kV. This reduction ensures that synchronization can still be performed even when the system voltage reaches 155–157 kV. Based on these findings, the study provides technical recommendations for system operators to adjust the tap positions accurately, ensuring reliable synchronization of the power plant with the interconnected system safely and effectively under overvoltage conditions.